Objective classification of countermovement jump force-time curve modality: within athlete-consistency and associations with jump performance - Bayne, H.; Cockcroft, J.; Robyn, A.; Louw, Q. (Sports Biomechanics, 2024)
Force-time curves produced during a countermovement jump (CMJ) have traditionally been classified by visual observation as either unimodal (one concentric phase peak) or bimodal (two peaks). The association between CMJ modality and jump performance remains unclear and future studies may benefit from standardising and expanding modality classification. This study described a numerical method based on the timing and relative magnitude of concentric force-time curve prominences. Adult male elite rugby union players (n=214) performed six CMJs on a force-instrumented treadmill and an algorithm using turning-point logic was applied to categorise jumps and define modality sub-groups. A sensitivity analysis demonstrated that the minimum prominence threshold (MPT) affected categorisation, as the proportion of bimodal jumps decreased with each 1% increase in MPT. Within-athlete consistency was also affected; between 43% and 63% of participants were consistently categorised as bimodal or unimodal depending on the selected MPT. Modified reactive strength index (RSImod), but not jump height or take-off momentum, was greater in unimodal jumps. Take-off momentum and RSImod were greater in subcategories where maximum force occurred early in the concentric phase. Future research should implement objective classification methods to enhance transparency and comparability and consider subcategories to investigate CMJ force production strategies.